Understanding Political Economy Analysis and Thinking and Working Politically - Whaites, Alan; Piron, Laure-Hélène; Menocal, Alina Rocha; Teskey, Graham (FCDO and TWP CoP, 2023)
This guide is adapted from work by the UK Foreign, Commonwealth and Development Office (FCDO) with inputs from members of the Thinking and Working Politically Community of Practice (TWP CoP). It outlines how to understand and use a set of analytical tools that are collectively known as Political Economy Analysis (PEA). The guide aims to equip practitioners to act in an informed manner, given that development objectives are invariably politically complex, and entail engaging with counterparts’ political incentives and preferences. The guide summarises different types of tools – from very light-touch to more in-depth approaches – and provides advice on how development professionals can decide what is most appropriate in a given context, with illustrations based on the experiences of teams working on these issues. This guide will help development professionals and others to make use of PEA and to apply it to their own specific needs. The first part of the guide offers a general picture of the approach. The second part provides more specific guidance for those who are tasked with deploying a PEA. Contents –> Main audience What is PEA, its role and purpose (Section 2) –> General information for all readers The main elements of PEA (Section 3) Thinking and Working Politically (Section 4) –> Core information for teams planning and using PEA How to ensure quality (Section 5) –> Essential reading for those directly responsible for a PEA Important concepts and terminology (Annex) –> General information for all readers

Applied political economy analysis for human rights programs and campaigns: A guide for practitioners (second edition) - Pact (Pact, 2023)
This updated guide provides practical guidance to practitioners in the human rights sector and beyond on how to integrate Applied Political Economy Analysis